PERFORMANCE IMPROVEMENT OF RADON COUNTERS. - Yong-Cheol Kim, Gyu-Sik Kim (International Journal of Research Science and Management, 2017)
In order to calibrate Siren PRO3 radon counter, the ion chamber-type radon counter RD200 and the radon measuring apparatus RAD7 were used. Through some experimental studies, we found that the performance of the Siren PRO3 could be improved using a linear regression analysis technique.